Toner for electrostatic image development, electrostatic image developer, and toner cartridge

By using Si-doped strontium titanate particles and silica particles with specific particle size distribution in the toner for electrostatic image development, the problem of image blurring is solved, and a clearer and more stable image formation is achieved.

CN112540517BActive Publication Date: 2025-03-28FUJIFILM BUSINESS INNOVATION CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202010151214.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-20
Filing Date
2020-03-06
Publication Date
2025-03-28
Estimated Expiration
2040-03-06

AI Technical Summary

Technical Problem

The conventional toner for electrostatic image development is difficult to suppress the occurrence of image blur, especially in high temperature and high humidity environments.

Method used

The toner for electrostatic image development including toner particles, Si-doped strontium titanate particles and silica particles is used, wherein the particle size of at least one peak in the particle size distribution of the silica particles is greater than the median diameter D50 of the Si-doped strontium titanate particles.

Benefits of technology

It effectively suppresses the occurrence of image blurring and improves the sharpness and stability of the image.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002402497480000281
    Figure BDA0002402497480000281
  • Figure BDA0002402497480000291
    Figure BDA0002402497480000291
  • Figure BDA0002402497480000301
    Figure BDA0002402497480000301
Patent Text Reader

Abstract

The present invention relates to a toner for electrostatic image development, an electrostatic image developer, and a toner cartridge. The toner for electrostatic image development comprises toner particles, Si-doped strontium titanate particles, and silicon dioxide particles, wherein at least one peak in the particle size distribution of primary particles of the silicon dioxide particles based on the number of particles is larger than the median diameter D of the primary particles of the Si-doped strontium titanate particles based on the number of particles. 50 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a toner for developing an electrostatic image, an electrostatic image developer, and a toner cartridge. Background Art

[0002] Japanese Patent Application Laid-Open No. 2005-148405 discloses an electrophotographic toner including toner base particles, strontium titanate fine particles, and hydrophobic inorganic fine particles having an average particle diameter of 1 / 10 to 1 / 3 of the average particle diameter of the strontium titanate fine particles.

[0003] Japanese Patent Application Laid-Open No. 2011-203758 discloses a developer containing, as abrasive particles, strontium titanate particles having an average primary particle diameter of 30 nm to 300 nm.

[0004] Japanese Patent Application Laid-Open No. 2018-200395 discloses a toner having toner particles, strontium titanate particles having a primary particle number average particle diameter of 10 nm to 80 nm, and fumed silica.

[0005] Japanese Patent Application Laid-Open No. 2019-028235 discloses a toner for electrostatic image development, which contains toner particles, silica particles, and strontium titanate particles having an average primary particle size of 10 nm to 100 nm. Summary of the invention

[0006] Technical problem to be solved by the invention

[0007] The technical problem to be solved by the present invention is to provide a toner for electrostatic image development, comprising toner particles, Si-doped strontium titanate particles and silicon dioxide particles, wherein the particle diameters of all peaks in the particle diameter distribution based on the number of primary particles of the silicon dioxide particles are smaller than the median diameter D based on the number of primary particles of the Si-doped strontium titanate particles. 50 The electrostatic image developing toner of the present invention can suppress the occurrence of image fogging as compared with the electrostatic image developing toner of the present invention.

[0008] According to a first aspect of the present invention, there is provided a toner for developing an electrostatic image, wherein:

[0009] The toner contains toner particles, Si-doped strontium titanate particles and silicon dioxide particles.

[0010] The particle size D of at least one peak in the particle size distribution based on the number of primary particles of the silicon dioxide particles is larger than the median diameter D based on the number of primary particles of the Si-doped strontium titanate particles. 50 .

[0011] According to a second aspect of the present invention, the molar amount of Si contained in the Si-doped strontium titanate particles is 0.25 mol% to 10 mol% relative to the molar amount of Sr.

[0012] According to a third aspect of the present invention, the molar amount of Si contained in the Si-doped strontium titanate particles is 1 mol% to 5 mol% relative to the molar amount of Sr.

[0013] According to the fourth aspect of the present invention, the median diameter D of the Si-doped strontium titanate particles is 50 It is greater than 30nm and less than 80nm.

[0014] According to the fifth aspect of the present invention, the median diameter D of the Si-doped strontium titanate particles is 50 It is greater than 30nm and less than 60nm.

[0015] According to a sixth aspect of the present invention, the particle size D of the silica particles is not less than 40 nm and not more than 120 nm.

[0016] According to a seventh aspect of the present invention, the particle size D of the silica particles is not less than 60 nm and not more than 110 nm.

[0017] According to the eighth aspect of the present invention, the median diameter D of the Si-doped strontium titanate particles is 50 The particle size D of at least one peak in the particle size distribution based on the number of primary particles of the silica particles satisfies 10 nm ≤ DD 50 ≦100nm.

[0018] According to the ninth aspect of the present invention, the median diameter D of the Si-doped strontium titanate particles is 50 The particle size D of at least one peak in the particle size distribution based on the number of primary particles of the silica particles satisfies 20 nm ≤ DD 50 ≦90nm.

[0019] According to a tenth aspect of the present invention, the silica particles include sol-gel silica particles.

[0020] The particle size D of at least one peak composed of sol-gel silica particles in the particle size distribution based on the number of primary particles of the silica particles is larger than the median diameter D based on the number of primary particles of the Si-doped strontium titanate particles. 50 .

[0021] According to the eleventh aspect of the present invention, the median diameter D of the Si-doped strontium titanate particles is 50 The particle size D of at least one peak formed by the sol-gel silica particles satisfies 10 nm ≤ DD 50≦100nm.

[0022] According to a twelfth aspect of the present invention, the water content of the sol-gel silica particles is 1 mass % or more and 10 mass % or less.

[0023] According to the 13th aspect of the present invention, the content M1 of the Si-doped strontium titanate particles is greater than the median diameter D of the Si-doped strontium titanate particles. 50 The content M2 of the silica particles satisfies the relationship of 1.2≦M2 / M1≦5.0 on a mass basis.

[0024] According to a fourteenth aspect of the present invention, there is provided an electrostatic image developer comprising the above-mentioned electrostatic image developing toner.

[0025] According to a fifteenth aspect of the present invention, there is provided a toner cartridge that is detachably mounted in an image forming apparatus and stores the above-mentioned toner for developing an electrostatic image.

[0026] Effects of the Invention

[0027] According to the first aspect, there is provided a toner for electrostatic image development, comprising toner particles, Si-doped strontium titanate particles and silica particles, wherein the particle sizes of all peaks in the particle size distribution based on the number of primary particles of the silica particles are smaller than the median diameter D based on the number of primary particles of the Si-doped strontium titanate particles. 50 The electrostatic image developing toner provided by the embodiment can suppress the occurrence of image blurring compared with the electrostatic image developing toner of the present invention.

[0028] According to the above-mentioned second embodiment, a toner for electrostatic image development is provided, which can suppress the occurrence of image blurring compared with the case where the molar amount of Si contained in the Si-doped strontium titanate particles is less than 0.25 mol% or greater than 10 mol% relative to the molar amount of Sr.

[0029] According to the above-mentioned third scheme, a toner for electrostatic image development is provided, which can suppress the occurrence of image blurring compared with the case where the molar amount of Si contained in the Si-doped strontium titanate particles is less than 1 mol% or greater than 5 mol% relative to the molar amount of Sr.

[0030] According to the fourth aspect, there is provided a toner for electrostatic image development, wherein the primary particles of Si-doped strontium titanate particles have a median diameter D based on the number of particles. 50 The electrostatic image developing toner provided by this embodiment can suppress the occurrence of image fogging compared with the case where the particle size is less than 30 nm or greater than 80 nm.

[0031] According to the fifth aspect, there is provided a toner for electrostatic image development, wherein the primary particles of Si-doped strontium titanate particles have a median diameter D based on the number of particles. 50 The electrostatic image developing toner provided by this embodiment can suppress the occurrence of image fogging compared with the case where the particle size is less than 30 nm or greater than 60 nm.

[0032] According to the above-mentioned sixth scheme, a toner for electrostatic image development is provided, which can suppress the occurrence of image blurring compared with the case where the particle sizes of all peaks in the particle size distribution based on the number of primary particles of silica particles are less than 40nm or greater than 120nm.

[0033] According to the above-mentioned seventh scheme, a toner for electrostatic image development is provided, which can suppress the occurrence of image blurring compared with the case where the particle sizes of all peaks in the particle size distribution based on the number of primary particles of silica particles are less than 60nm or greater than 110nm.

[0034] According to the eighth aspect, there is provided a toner for electrostatic image development, wherein the primary particles of Si-doped strontium titanate particles have a median diameter D based on the number of particles. 50 The particle diameter D of all peaks in the particle diameter distribution based on the number of primary particles of the silica particles does not satisfy 10 nm ≤ DD. 50 Compared with the case where the relationship of ≦100 nm is maintained, the electrostatic image developing toner provided by this embodiment can suppress the occurrence of image fogging.

[0035] According to the ninth aspect, there is provided a toner for electrostatic image development, wherein the primary particles of Si-doped strontium titanate particles have a median diameter D based on the number of particles. 50 The particle diameter D of all peaks in the particle diameter distribution based on the number of primary particles of the silica particles does not satisfy 20 nm ≤ DD 50 The electrostatic image developing toner provided by this embodiment can suppress the occurrence of image fogging, compared with the case where the relationship of ≦90 nm is maintained.

[0036] According to the tenth aspect, there is provided a toner for developing an electrostatic image, which can suppress the occurrence of image fogging compared with the case where the silica particles are only fumed silica particles.

[0037] According to the eleventh aspect, there is provided a toner for electrostatic image development, wherein the primary particles of Si-doped strontium titanate particles have a median diameter D based on the number of particles. 50 The particle diameter D of all peaks composed of sol-gel silica particles in the particle size distribution based on the number of primary particles of silica particles does not satisfy 10 nm ≤ DD 50Compared with the case where the relationship of ≦100 nm is maintained, the electrostatic image developing toner provided by this embodiment can suppress the occurrence of image fogging.

[0038] According to the twelfth aspect, there is provided a toner for electrostatic image development, which can suppress the occurrence of image blurring compared with the case where the water content of the sol-gel silica particles is less than 1 mass % or greater than 10 mass %.

[0039] According to the thirteenth aspect, there is provided a toner for developing an electrostatic image, wherein the content M1 of Si-doped strontium titanate particles is greater than the median diameter D of the Si-doped strontium titanate particles. 50 The electrostatic image developing toner provided by this embodiment can suppress the occurrence of image blurring, compared with a case where the content M2 of the silica particles does not satisfy the relationship of 1.2≦M2 / M1≦5.0 on a mass basis.

[0040] According to the above-mentioned 14th aspect, there is provided an electrostatic image developer, wherein the electrostatic image developing toner comprises toner particles, Si-doped strontium titanate particles and silica particles, and the particle diameters of all peaks in the particle diameter distribution based on the number of primary particles of the silica particles are smaller than the median diameter D based on the number of primary particles of the Si-doped strontium titanate particles. 50 The electrostatic image developer provided by the embodiment can suppress the occurrence of image blur compared with the case of.

[0041] According to the fifteenth aspect, there is provided a toner cartridge, wherein a toner for electrostatic image development comprises toner particles, Si-doped strontium titanate particles and silica particles, wherein the particle diameters of all peaks in the particle diameter distribution based on the number of primary particles of the silica particles are smaller than the median diameter D based on the number of primary particles of the Si-doped strontium titanate particles. 50 Compared with the case of FIG. 1 , the toner cartridge provided by this scheme can suppress the occurrence of image blur. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a schematic structural diagram showing an example of the image forming apparatus according to the present embodiment.

[0043] Figure 2 This is a schematic structural diagram showing an example of a process cartridge that is attached to and detached from the image forming apparatus according to the present embodiment. DETAILED DESCRIPTION

[0044] The following describes embodiments of the present invention. These descriptions and examples are intended to illustrate the embodiments and do not limit the scope of the embodiments.

[0045] In the present invention, the numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the minimum value and the maximum value, respectively.

[0046] In the numerical range recorded in stages among the present invention, the upper limit or lower limit recorded in a numerical range can be replaced by the upper limit or lower limit of the numerical range in other stages recorded. In addition, in the numerical range recorded in the present invention, the upper limit or lower limit of this numerical range can be replaced by the value shown in the embodiment.

[0047] The term "step" in the present invention includes not only an independent step but also a step that cannot be clearly distinguished from other steps as long as the intended purpose of the step can be achieved.

[0048] When the embodiments of the present invention are described with reference to the drawings, the configuration of the embodiments is not limited to the configuration shown in the drawings. In addition, the sizes of the components in the drawings are schematic, and the relative relationship between the sizes of the components is not limited to this.

[0049] Each component in the present invention may contain two or more corresponding substances. When referring to the amount of each component in the composition of the present invention, if there are two or more substances corresponding to each component in the composition, unless otherwise stated, it refers to the total amount of the two or more substances present in the composition.

[0050] The particles corresponding to each component in the present invention may include two or more kinds of particles. When two or more kinds of particles corresponding to each component are present in the composition, unless otherwise stated, the particle size of each component refers to the value for the mixture of the two or more kinds of particles present in the composition.

[0051] In the present invention, “toner for developing an electrostatic image” is also simply referred to as “toner”, and “developer for developing an electrostatic image” is also simply referred to as “developer”.

[0052] <Toner for Electrostatic Image Development>

[0053] The toner according to this embodiment includes toner particles, Si-doped strontium titanate particles, and silica particles.

[0054] The particle diameter D of at least one peak in the particle diameter distribution based on the number of primary particles of the silica particles contained in the toner of the present embodiment is larger than the median diameter D based on the number of primary particles of the Si-doped strontium titanate particles. 50 .

[0055] The toner of this embodiment can suppress the occurrence of image blurring. “Image blurring” is a phenomenon in which an undesired dot-shaped image appears on the image forming surface of a recording medium. The mechanism by which the toner of this embodiment suppresses the occurrence of image blurring is presumed to be as follows.

[0056] Strontium titanate particles are known as an external additive for toner, and the strontium titanate particles are externally added to toner as a charge control agent, abrasive, or the like.

[0057] According to the research of the present inventors, when forming images using a toner with strontium titanate particles added externally, image blurring may occur, especially when low-density images are intermittently formed in a high-temperature and high-humidity environment (e.g., temperature 30°C and relative humidity 85%), and then high-density images are continuously formed in a low-temperature and low-humidity environment (e.g., temperature 10°C and relative humidity 15%). It is presumed that this is caused by the following phenomenon occurring in the developing mechanism.

[0058] In a high temperature and high humidity environment, the toner particles become relatively soft, and low-density images with slow toner consumption are continuously formed, causing the toner to be stirred for a long time in the developing mechanism, and the strontium titanate particles are buried in the toner particles. When high-density images are formed continuously thereafter, the toner in the developing mechanism is consumed, and the toner consumed is replenished to the developing mechanism. The toner without strontium titanate particles and the toner without strontium titanate particles are mixed in the developing mechanism, that is, toners with different surface properties are mixed in the developing mechanism.

[0059] Furthermore, when toners with different surface properties rub against each other, friction charging occurs between these toners, that is, charge transfer occurs from one toner to another (particularly likely to occur in a low-temperature and low-humidity environment), resulting in toners with insufficient charge. Toners with insufficient charge do not adhere to the image holder during development and scatter, resulting in blurred images.

[0060] According to further studies by the present inventors, the occurrence of image blur in the above-mentioned imaging is suppressed by externally adding silicon dioxide particles having a larger particle size than the strontium titanate particles and doping the strontium titanate particles with Si (silicon).

[0061] First, the presence of relatively large silica particles on the toner particle surfaces is presumably responsible for suppressing collisions between the toner particles and strontium titanate particles on the toner particle surfaces, thereby suppressing burial of the strontium titanate particles in the toner particles.

[0062] In addition, by doping Si into strontium titanate particles, the position of strontium titanate particles in the friction charging sequence becomes close to that of silica particles. It is speculated that compared with the toner particles added with undoped Si-strontium titanate particles and silica particles, the toner to which Si-doped strontium titanate particles and silica particles are added is less likely to cause friction charging between toners.

[0063] Therefore, it can be inferred that the toner of this embodiment is not likely to cause frictional charging between toner particles even when performing the above-mentioned imaging, and can suppress the mixing of toner with insufficient charge and the scattering of toner, thereby suppressing the occurrence of image blur.

[0064] The method for measuring the particle diameters of the Si-doped strontium titanate particles and the silica particles contained in the toner of the present embodiment is as follows.

[0065] The toner is dispersed in methanol, and then centrifuged after applying ultrasonic waves to precipitate the toner particles, and the supernatant containing the external additive is recovered. A density gradient solution (e.g., a density gradient solution of sodium polytungstate or cesium chloride) is prepared in another centrifuge tube, and the supernatant is separated into layers (heavy layer) and centrifuged. The fraction containing the silicon dioxide particles and the fraction containing the Si-doped strontium titanate particles are extracted based on their respective densities, and dried to obtain the respective particles.

[0066] Next, add the silica particles (or Si-doped strontium titanate particles) to an aqueous electrolyte solution (isotonic aqueous solution), apply ultrasound for more than 30 seconds, and disperse into a state of primary particles. Use the dispersion as a sample, and use a laser diffraction scattering particle size distribution measuring device (e.g., Microtrac MT3000II manufactured by Microtrac BEL) to measure the particle size of at least 3,000 particles. For silica particles, draw a frequency distribution based on the number of particles from the small diameter side to find the particle size of each peak. For Si-doped strontium titanate particles, draw a cumulative distribution based on the number of particles from the small diameter side to find the median diameter D 50 (Particle size at the cumulative 50% point).

[0067] The components, structure, and characteristics of the toner according to this embodiment are described in detail below.

[0068] [Toner particles]

[0069] The toner particles are constituted by, for example, containing a binding resin and, if necessary, a colorant, a release agent, and other additives.

[0070] - Adhesive resin -

[0071] As the adhesive resin, for example, there can be mentioned a vinyl resin formed by a homopolymer of the following monomers or a copolymer of two or more of these monomers, the monomers being: styrenes (for example, styrene, p-chlorostyrene, α-methylstyrene, etc.), (meth)acrylates (for example, methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (for example, acrylonitrile, methacrylonitrile, etc.), vinyl ethers (for example, vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (for example, vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), olefins (for example, ethylene, propylene, butadiene, etc.), etc.

[0072] Examples of the adhesive resin include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosins, mixtures of these resins with the above-mentioned vinyl resins, or graft polymers obtained by polymerizing vinyl monomers in the coexistence of these resins.

[0073] These adhesive resins may be used alone or in combination of two or more.

[0074] As the adhesive resin, a polyester resin is suitable.

[0075] As the polyester resin, for example, a known amorphous polyester resin can be cited. Among the polyester resins, the amorphous polyester resin can also be used together with a crystalline polyester resin. Among them, the crystalline polyester resin can be used in a content of 2% by mass to 40% by mass (preferably 2% by mass to 20% by mass) relative to the total binder resin.

[0076] The "crystallinity" of a resin means that there is no step-like change in endothermic value in differential scanning calorimetry (DSC) and that the resin has a clear endothermic peak. Specifically, the half-width of the endothermic peak is within 10°C when measured at a heating rate of 10 (°C / min).

[0077] On the other hand, the "amorphous" nature of a resin means that the half-peak width is larger than 10°C, the endothermic quantity changes stepwise, or no clear endothermic peak is observed.

[0078] Amorphous polyester resin

[0079] Examples of the non-crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. As the non-crystalline polyester resin, a commercially available product may be used, or a synthetic product may be used.

[0080] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenyl succinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexane dicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, etc.), anhydrides thereof, or lower (e.g., carbon number 1 to 5) alkyl esters thereof. Among these, aromatic dicarboxylic acids are preferred as the polycarboxylic acid.

[0081] Among the polycarboxylic acids, dicarboxylic acids and trivalent or higher carboxylic acids having a crosslinked structure or a branched structure may be used in combination. Examples of trivalent or higher carboxylic acids include trimellitic acid, pyromellitic acid, their anhydrides, or their lower (e.g., carbon number 1 to 5) alkyl esters.

[0082] The polyvalent carboxylic acid may be used alone or in combination of two or more.

[0083] Examples of the polyol include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, the polyol is preferably an aromatic diol or an alicyclic diol, and more preferably an aromatic diol.

[0084] As the polyol, a diol may be used in combination with a trivalent or higher polyol having a crosslinked structure or a branched structure. Examples of the trivalent or higher polyol include glycerin, trimethylolpropane, and pentaerythritol.

[0085] The polyols may be used alone or in combination of two or more.

[0086] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C to 80°C, and more preferably 50°C to 65°C.

[0087] The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, by "extrapolated glass transition start temperature" described in the method for measuring glass transition temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics".

[0088] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 to 1,000,000, and more preferably 7,000 to 500,000.

[0089] The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less.

[0090] The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less.

[0091] The weight average molecular weight and the number average molecular weight were measured by gel permeation chromatography (GPC). In the molecular weight measurement using GPC, a Tosoh GPC HLC-8120GPC was used as a measuring device, a Tosoh column TSKgel SuperHM-M (15 cm) was used, and the measurement was performed using THF solvent. The weight average molecular weight and the number average molecular weight were calculated based on the measurement results using a molecular weight calibration curve prepared using a monodisperse polystyrene standard sample.

[0092] The amorphous polyester resin is obtained by a known production method. Specifically, for example, the amorphous polyester resin is obtained by setting the polymerization temperature to 180° C. to 230° C., reducing the pressure in the reaction system as necessary, and reacting while removing water or alcohol generated during condensation.

[0093] When the monomer of the raw material is insoluble or incompatible at the reaction temperature, a high boiling point solvent may be added as a dissolving aid to dissolve it. In this case, the polycondensation reaction is carried out while the dissolving aid is distilled off. When there are monomers with poor compatibility in the copolymerization reaction, the monomers with poor compatibility may be condensed with a specific acid or alcohol that is polycondensed with the monomer in advance, and then polycondensed with the main component.

[0094] Crystalline polyester resin

[0095] Examples of the crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. As the crystalline polyester resin, a commercially available product may be used, or a synthetic product may be used.

[0096] Here, in order to make the crystalline polyester resin easily form a crystal structure, the crystalline polyester resin is preferably a polycondensate obtained using a linear aliphatic polymerizable monomer rather than a polycondensate obtained using a polymerizable monomer having an aromatic ring.

[0097] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, or lower (e.g., carbon number 1 to 5) alkyl esters thereof.

[0098] Among the polycarboxylic acids, dicarboxylic acids and trivalent or higher carboxylic acids having a crosslinked structure or a branched structure may be used in combination. Examples of trivalent carboxylic acids include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, or their lower (e.g., carbon number 1 to 5) alkyl esters.

[0099] As the polycarboxylic acid, these dicarboxylic acids may be used in combination with a dicarboxylic acid having a sulfonic acid group or a dicarboxylic acid having an ethylenic double bond.

[0100] The polyvalent carboxylic acid may be used alone or in combination of two or more.

[0101] Examples of the polyol include aliphatic diols (e.g., linear aliphatic diols having a main chain portion having carbon atoms of 7 or more and 20 or less). Examples of the aliphatic diols include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosandiol. Among these, preferred aliphatic diols include 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol.

[0102] Among the polyols, diols may be used in combination with trivalent or higher alcohols having a crosslinked structure or a branched structure. Examples of the trivalent or higher alcohols include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol.

[0103] The polyols may be used alone or in combination of two or more.

[0104] Here, the content of the aliphatic diol in the polyol is preferably 80 mol % or more, and preferably 90 mol % or more.

[0105] The melting temperature of the crystalline polyester resin is preferably 50°C to 100°C, more preferably 55°C to 90°C, and even more preferably 60°C to 85°C.

[0106] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) by the “melting peak temperature” described in the method for measuring melting temperature in JIS K7121:1987 “Method for measuring transition temperatures of plastics”.

[0107] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.

[0108] The crystalline polyester resin can be obtained, for example, by a known production method similar to the amorphous polyester.

[0109] The content of the binder resin is preferably 40% by mass to 95% by mass, more preferably 50% by mass to 90% by mass, and further preferably 60% by mass to 85% by mass, based on the entire toner particles.

[0110] -Colorants-

[0111] Examples of the colorant include carbon black, chrome yellow, Hansa yellow, benzidine yellow, vat yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, sulfur-resistant orange, Vochug red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont Oil Red, pyrazolone red, litho red, rhodamine B lake, lake red C, pigment red, rose red, aniline blue, ultramarine blue, oil-soluble blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, malachite green oxalate and other pigments; and dyes such as acridine, xanthene, azo, benzoquinone, azine, anthraquinone, thioindigo, dioxazine, thiazine, azomethine, indigo, phthalocyanine, nigrosine, polymethine, triphenylmethane, diphenylmethane and thiazole.

[0112] The coloring agent may be used alone or in combination of two or more.

[0113] The colorant may be a colorant that has been subjected to a surface treatment as required, or may be used in combination with a dispersant. In addition, two or more colorants may be used in combination.

[0114] The content of the colorant is preferably from 1 mass % to 30 mass % both inclusive, and more preferably from 3 mass % to 15 mass % both inclusive, based on the entire toner particles.

[0115] -Release agent-

[0116] Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic waxes such as montan wax, or mineral and petroleum waxes, and ester waxes such as fatty acid esters and montanic acid esters. The release agent is not limited thereto.

[0117] The melting temperature of the release agent is preferably 50°C to 110°C, more preferably 60°C to 100°C.

[0118] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) by the “melting peak temperature” described in the method for measuring melting temperature in JIS K7121:1987 “Method for measuring transition temperatures of plastics”.

[0119] The content of the release agent is preferably from 1 mass % to 20 mass % both inclusive, and more preferably from 5 mass % to 15 mass % both inclusive, based on the entire toner particles.

[0120] -Other additives-

[0121] Examples of other additives include known additives such as magnetic materials, charge control agents, and inorganic powders. These additives may be contained in the toner particles as internal additives.

[0122] -Characteristics of toner particles, etc.-

[0123] The toner particles may be toner particles of a single-layer structure, or may be toner particles of a so-called core / shell structure composed of a core portion (core particle) and a coating layer (shell layer) that covers the core portion.

[0124] The toner particles of a core / shell structure may be composed of, for example, a core portion including a binder resin and, if necessary, other additives such as a colorant and a release agent, and a coating layer including a binder resin.

[0125] The volume average particle diameter (D50v) of the toner particles is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm.

[0126] The volume average particle size (D50v) of the toner particles is measured using Coulter Multisizer II (manufactured by Beckman Coulter) and the electrolyte is measured using ISOTON-II (manufactured by Beckman Coulter).

[0127] In the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and then added to 100 ml to 150 ml of the electrolyte.

[0128] The electrolyte in which the sample is suspended is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with a particle size of 2 μm or more and 60 μm or less is measured using a Coulter Multisizer II with a hole of 100 μm. The number of particles sampled is 50,000. The volume-based particle size distribution is drawn from the small diameter side, and the particle size at the cumulative 50% point is taken as the volume average particle size D50v.

[0129] The average circularity of the toner particles is preferably from 0.94 to 1.00, and more preferably from 0.95 to 0.98.

[0130] The average circularity of the toner particles is calculated by (equivalent circular circumference) / (circumference) [(circumference of a circle having the same projected area as the particle image) / (circumference of the particle projected image)]. Specifically, it is a value measured by the following method.

[0131] First, the toner particles to be measured are collected by suction and formed into a flat flow, and the particles are momentarily strobed to obtain a particle image as a still image, and the particle image is analyzed by a flow particle image analyzer (FPIA-3000 manufactured by Sysmex) to obtain the average circularity. The number of samples for obtaining the average circularity is set to 3500.

[0132] When the toner has an external additive, the toner (developer) to be measured is dispersed in water containing a surfactant and then subjected to ultrasonic treatment to obtain toner particles from which the external additive has been removed.

[0133] [Si-doped strontium titanate particles]

[0134] The median diameter D of the Si-doped strontium titanate particles in the present invention is 50 The median diameter D of the primary particles based on the number of particles 50 .

[0135] Si-doped strontium titanate particles are strontium titanate particles doped with at least Si, and may be doped with Si and elements other than Si, Sr, Ti and O (e.g., metal elements other than Si, Sr and Ti). Si-doped strontium titanate particles may be used alone or in combination of two or more.

[0136] The molar amount of Si contained in the Si-doped strontium titanate particles relative to the molar amount of Sr is preferably 0.25 mol% or more and 10 mol% or less. The molar amount of Si contained in the Si-doped strontium titanate particles relative to the molar amount of Sr is also referred to as "Si doping amount" hereinafter. The Si doping amount of the Si-doped strontium titanate particles can be confirmed by fluorescent X-ray analysis.

[0137] From the perspective of making the triboelectric charging sequence of the Si-doped strontium titanate particles close to that of the silica particles, the Si doping amount of the Si-doped strontium titanate particles is preferably 0.25 mol % or more, more preferably 0.5 mol % or more, and even more preferably 1 mol % or more.

[0138] In addition, the particle shape of strontium titanate particles is usually a cube or a cuboid. It is presumed that if Si is doped, the crystallinity of strontium titanate decreases, and the particle shape becomes a curved shape, which is not easily buried in the toner particles. From this point of view, it is also preferred that the Si doping amount is within the above range.

[0139] From the perspective of growing crystals to a desired particle size when manufacturing Si-doped strontium titanate particles, and from the perspective of expecting a charge control effect on Si-doped strontium titanate particles, the Si doping amount of Si-doped strontium titanate particles is preferably 10 mol% or less, more preferably 7 mol% or less, and even more preferably 5 mol% or less.

[0140] From the viewpoint that Si-doped strontium titanate particles are not easily buried in toner particles, the median diameter D of the Si-doped strontium titanate particles is 50 The median diameter D of the Si-doped strontium titanate particles is preferably 30 nm or more, and more preferably 35 nm or more. 50 It is preferably 80 nm or less, more preferably 70 nm or less, and even more preferably 60 nm or less.

[0141] The amount of the Si-doped strontium titanate particles added is preferably 0.3 to 5 parts by mass, more preferably 0.5 to 3 parts by mass, and further preferably 0.5 to 2 parts by mass, relative to 100 parts by mass of the toner particles.

[0142] -Method for producing Si-doped strontium titanate particles-

[0143] The Si-doped strontium titanate particles may be Si-doped strontium titanate particles themselves or particles whose surfaces have been hydrophobized. The method for producing the Si-doped strontium titanate particles is not particularly limited, but a wet method is preferred from the perspective of controlling the particle size.

[0144] ·Manufacturing of Si-doped strontium titanate particles

[0145] The wet method for preparing Si-doped strontium titanate particles is, for example, the following method: adding an alkaline aqueous solution to a mixture of a titanium oxide source, a strontium source, and a dopant source to react, followed by acid treatment. In this method, the particle size of the Si-doped strontium titanate particles is controlled by the mixing ratio of the titanium oxide source and the strontium source, the concentration of the titanium oxide source at the initial stage of the reaction, the temperature and the addition rate when the alkaline aqueous solution is added, etc.

[0146] As the titanium oxide source, an inorganic acid hydrolyzate of a titanium compound is preferred. As the strontium source, strontium nitrate, strontium chloride, etc. may be mentioned.

[0147] The mixing ratio of the titanium oxide source and the strontium source is preferably 0.9 to 1.4, more preferably 1.05 to 1.20, in terms of Sr / Ti molar ratio. 2 The concentration is preferably 0.05 mol / L to 1.3 mol / L, and more preferably 0.5 mol / L to 1.0 mol / L.

[0148] As the dopant source, an oxide of Si (e.g., silicon dioxide) can be cited. The Si oxide as the dopant source is added in the form of a solution dissolved in nitric acid, hydrochloric acid, or sulfuric acid, for example. The amount of the dopant source added is preferably an amount such that the Si contained in the dopant source is 0.25 mol to 10 mol relative to 100 mol of Sr contained in the strontium source, more preferably 0.5 mol to 7 mol, and further preferably 1 mol to 5 mol.

[0149] As the aqueous alkali solution, an aqueous sodium hydroxide solution is preferred. The higher the temperature of the reaction solution when the aqueous alkali solution is added, the more crystalline particles can be obtained. The temperature of the reaction solution when the aqueous alkali solution is added is, for example, in the range of 60°C to 100°C. The slower the addition rate of the aqueous alkali solution, the larger the particle size of the particles, and the faster the addition rate, the smaller the particle size of the particles. Relative to the raw materials input, the addition rate of the aqueous alkali solution is, for example, preferably 0.001 equivalents / h to 1.2 equivalents / h, and more preferably 0.002 equivalents / h to 1.1 equivalents / h.

[0150] After adding the alkaline aqueous solution, an acid treatment is performed to remove the unreacted strontium source. The acid treatment uses, for example, hydrochloric acid to adjust the pH of the reaction solution to 2.5 to 7.0, more preferably 4.5 to 6.0. After the acid treatment, the reaction solution is separated into solid and liquid, and the solid component is dried to obtain Si-doped strontium titanate particles.

[0151] Surface treatment

[0152] Regarding the surface treatment of Si-doped strontium titanate particles, for example, a treatment solution is prepared by mixing a silicon-containing organic compound as a hydrophobic treatment agent with a solvent, and the Si-doped strontium titanate particles and the treatment solution are mixed under stirring, and further stirring is continued to perform the surface treatment. After the surface treatment, a drying treatment is performed to remove the solvent of the treatment solution.

[0153] Examples of the silicon-containing organic compound used for the surface treatment of the Si-doped strontium titanate particles include alkoxysilane compounds, silazane compounds, silicone oils, and the like.

[0154] Examples of alkoxysilane compounds used for the surface treatment of Si-doped strontium titanate particles include tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, hexyltrimethoxysilane, n-octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, vinyltriethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, and butyltriethoxysilane. , hexyltriethoxysilane, decyltriethoxysilane, dodecyltriethoxysilane, phenyltrimethoxysilane, o-tolyltrimethoxysilane, p-tolyltrimethoxysilane, phenyltriethoxysilane, benzyltriethoxysilane; dimethyldimethoxysilane, dimethyldiethoxysilane, methylvinyldimethoxysilane, methylvinyldiethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane; trimethylmethoxysilane, trimethylethoxysilane.

[0155] Examples of the silazane compound used for the surface treatment of the Si-doped strontium titanate particles include dimethyldisilazane, trimethyldisilazane, tetramethyldisilazane, pentamethyldisilazane, and hexamethyldisilazane.

[0156] As silicone oils used in the surface treatment of Si-doped strontium titanate particles, for example, silicone oils such as dimethylpolysiloxane, diphenylpolysiloxane, and phenylmethylpolysiloxane; reactive silicone oils such as amino-modified polysiloxane, epoxy-modified polysiloxane, carboxyl-modified polysiloxane, methanol-modified polysiloxane, fluorine-modified polysiloxane, methacryloyl-modified polysiloxane, mercapto-modified polysiloxane, and phenol-modified polysiloxane; and the like.

[0157] As the solvent used in the preparation of the above-mentioned treatment liquid, when the silicon-containing organic compound is an alkoxysilane compound or a silazane compound, alcohol (such as methanol, ethanol, propanol, butanol) is preferred, and when the silicon-containing organic compound is silicone oil, hydrocarbons (such as benzene, toluene, n-hexane, n-heptane) are preferred.

[0158] In the treatment liquid, the concentration of the silicon-containing organic compound is preferably 1 mass % to 50 mass %, more preferably 5 mass % to 40 mass %, and further preferably 10 mass % to 30 mass %.

[0159] The amount of the silicon-containing organic compound used for the surface treatment is preferably 1 to 50 parts by mass, more preferably 5 to 40 parts by mass, and even more preferably 5 to 30 parts by mass, relative to 100 parts by mass of the Si-doped strontium titanate particles.

[0160] [Silicon dioxide particles]

[0161] In the present invention, the particle size distribution of the silica particles is a particle size distribution based on the number of primary particles.

[0162] The particle size distribution of the silica particles added to the toner of this embodiment may be unimodal or multimodal, wherein the particle size D of at least one peak in the particle size distribution is larger than the median size D of the Si-doped strontium titanate particles. 50 .

[0163] As an embodiment (1) of the silicon dioxide particles, a particle size distribution having a single peak and a particle size of the peak being larger than the median diameter D of the Si-doped strontium titanate particles can be cited. 50 way.

[0164] As an embodiment (2) of the silica particles, a particle size distribution having a bimodal distribution and a particle size of the peak on the larger diameter side being larger than the median diameter D of the Si-doped strontium titanate particles can be cited. 50 The particle size of the peak on the small diameter side is smaller than the median diameter D of the Si-doped strontium titanate particles. 50 Or with median diameter D 50 From the viewpoint of further suppressing the occurrence of image blur, the amount of silica particles constituting the peak on the larger diameter side is preferably greater than the amount of silica particles constituting the peak on the smaller diameter side (based on mass).

[0165] As an embodiment (3) of the silica particles, a particle size distribution is bimodal and the particle size of the peak on the large diameter side and the particle size of the peak on the small diameter side are both larger than the median diameter D of the Si-doped strontium titanate particles. 50 From the perspective of further suppressing the occurrence of image blur, the amount of silica particles constituting the peak on the smaller diameter side is preferably greater than the amount of silica particles constituting the peak on the larger diameter side (based on mass).

[0166] As an embodiment (4) of the silica particles, a particle size distribution having a trimodal distribution and a particle size of the large-diameter peak and a particle size of the middle peak are both larger than the median diameter D of the Si-doped strontium titanate particles. 50 The particle size of the peak on the small diameter side is smaller than the median diameter D of the Si-doped strontium titanate particles. 50 Or with median diameter D 50 From the perspective of further suppressing the occurrence of image blur, the amount of silica particles constituting the intermediate peak is preferably greater than the amount of silica particles constituting the large diameter side peak and the amount of silica particles constituting the small diameter side peak (based on mass).

[0167] When the particle size distribution of the silica particles is unimodal, the distribution may be narrow or broad.

[0168] When the particle size distribution of the silica particles is multimodal, the distribution may be in a form in which each peak is narrow or in a form in which each peak is broad.

[0169] From the viewpoint of further suppressing the occurrence of image blur, the particle size distribution of the silica particles is preferably unimodal and narrow, or multimodal (preferably bimodal or trimodal) with each peak having a narrow distribution.

[0170] In the present invention, “narrow peak distribution” of the silica particles means a mode in which the coefficient of variation of the distribution (a value obtained by dividing the standard deviation by the average value) is 20% or less.

[0171] Specifically, silica particles include fumed silica particles, wet silica particles, and fused silica particles. Sol-gel silica particles are more preferred as silica particles because of their narrow particle size distribution and their water content being within an appropriate range. Sol-gel silica particles generally have a narrow particle size distribution, and the coefficient of variation (the value obtained by dividing the standard deviation by the average value) of the particle size distribution of a production batch of sol-gel silica particles is, for example, 15% or less.

[0172] The sol-gel method for producing silica particles is well known. The sol-gel method includes, for example, mixing tetraalkoxysilane, water and alcohol and dropping ammonia water into the obtained mixed solution to prepare a silica sol suspension; centrifugally separating wet silica gel from the silica sol suspension; and drying the wet silica gel to obtain silica particles. Examples of tetraalkoxysilane include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane and the like.

[0173] Regarding the particle size of the primary particles of the silica particles, for example, when the silica particles are produced by the sol-gel method, it can be controlled by the stirring speed when preparing the silica sol suspension or the time required for preparing the silica sol suspension. The faster the stirring speed when preparing the silica sol suspension, the smaller the particle size of the primary particles of the silica particles. The longer the time required for preparing the silica sol suspension, the larger the particle size of the primary particles of the silica particles.

[0174] The surface of the silica particles is preferably subjected to hydrophobic treatment. The hydrophobic treatment is carried out by, for example, immersing the silica particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and for example, alkoxysilane compounds, silazane compounds (such as 1,1,1,3,3,3-hexamethyldisilazane), silicone oils (such as dimethyl silicone oil), titanate coupling agents, aluminum coupling agents, etc. can be cited. These treatment agents can be used alone or in combination with more than two. Typically, for example, relative to 100 parts by mass of silica particles, the amount of the hydrophobic treatment agent is 1 part by mass or less than 10 parts by mass.

[0175] In the silica particles, from the viewpoint of further suppressing the occurrence of image blur, it is preferred that the particle size D of at least one peak in the particle size distribution is larger than the median size D of the Si-doped strontium titanate particles. 50 The thickness is 40 nm to 120 nm, more preferably 50 nm to 110 nm, and even more preferably 60 nm to 110 nm.

[0176] In the above embodiment (2), the particle size of the peak on the large diameter side is preferably within the above range. In the above embodiment (3), the particle size of the peak on the small diameter side is preferably within the above range. In the above embodiment (4), the particle size of the intermediate peak is preferably within the above range.

[0177] The particle size D of at least one peak in the particle size distribution of the silicon dioxide particles is equal to the median diameter D of the Si-doped strontium titanate particles. 50 Preferably, 10nm≦DD 50 ≦100nm, preferably 20nm≦DD 50 ≦90nm, preferably 20nm≦DD 50 ≦80nm. The above relationship can further suppress the occurrence of image blur.

[0178] In the above embodiment (2), the particle size of the peak on the larger diameter side preferably satisfies the above relationship. In the above embodiment (3), the particle size of the peak on the smaller diameter side preferably satisfies the above relationship. In the above embodiment (4), the particle size of the intermediate peak preferably satisfies the above relationship.

[0179] From the perspective of further suppressing the occurrence of image blur, the silica particles preferably include sol-gel silica particles, and the particle size D of at least one peak composed of the sol-gel silica particles in the particle size distribution is larger than the median diameter D of the Si-doped strontium titanate particles. 50 The thickness is 40 nm to 120 nm, more preferably 50 nm to 110 nm, and even more preferably 60 nm to 110 nm.

[0180] In the above embodiment (2), it is preferred that the sol-gel silica particles constitute at least the peak on the large diameter side, and the particle size of the peak on the large diameter side is within the above range. In the above embodiment (3), it is preferred that the sol-gel silica particles constitute at least the peak on the small diameter side, and the particle size of the peak on the small diameter side is within the above range. In the above embodiment (4), it is preferred that the sol-gel silica particles constitute at least the intermediate peak, and the particle size of the intermediate peak is within the above range.

[0181] Here, the sol-gel silica particles having a particle size within the above range are preferably hydrophobicized sol-gel silica particles, and more preferably hydrophobicized silica particles using a silazane compound (preferably 1,1,1,3,3,3-hexamethyldisilazane).

[0182] From the perspective of further suppressing the occurrence of image blur, the silica particles preferably include sol-gel silica particles, and the particle size D of at least one peak composed of the sol-gel silica particles in the particle size distribution and the median diameter D of the Si-doped strontium titanate particles are equal to or greater than the median diameter D of the Si-doped strontium titanate particles. 50 Meeting 10nm≦DD 50 ≦100nm, preferably 20nm≦DD 50 ≦90nm, preferably 20nm≦DD 50 ≦80nm.

[0183] In the above embodiment (2), it is preferred that the sol-gel silica particles constitute at least the peak on the large diameter side, and the particle size of the peak on the large diameter side satisfies the above relationship. In the above embodiment (3), it is preferred that the sol-gel silica particles constitute at least the peak on the small diameter side, and the particle size of the peak on the small diameter side satisfies the above relationship. In the above embodiment (4), it is preferred that the sol-gel silica particles constitute at least the intermediate peak, and the particle size of the intermediate peak satisfies the above relationship.

[0184] Here, the sol-gel silica particles having a particle size satisfying the above relationship are preferably hydrophobicized sol-gel silica particles, and more preferably hydrophobicized silica particles using a silazane compound (preferably 1,1,1,3,3,3-hexamethyldisilazane).

[0185] The particle size is larger than the median diameter D of Si-doped strontium titanate particles. 50 In the sol-gel silica particles (including sol-gel silica particles that have been hydrophobized), from the perspective of further suppressing the occurrence of image blur, the water content is preferably from 1 mass % to 10 mass %, more preferably from 2 mass % to 8 mass %, and further preferably from 3 mass % to 6 mass %.

[0186] The water content of the sol-gel silica particles is measured as follows.

[0187] After the sample was allowed to stand in a chamber at a temperature of 22°C and a relative humidity of 55% for more than 20 hours for humidity control, it was heated from 30°C to 250°C at a heating rate of 30°C / min in a room at a temperature of 22°C and a relative humidity of 55% using a thermobalance (TGA-50 manufactured by Shimadzu Corporation) in a nitrogen atmosphere to measure the heating loss (mass loss due to heating). The moisture content was calculated by the following formula based on the heating loss.

[0188] Water content (mass %) = (weight loss after heating) ÷ (mass after humidity control and before heating) × 100

[0189] In the toner of this embodiment, the content M1 of the Si-doped strontium titanate particles is greater than the median diameter D of the Si-doped strontium titanate particles. 50 The content M2 of the silica particles preferably satisfies the relationship of 1.2≦M2 / M1≦5.0 on a mass basis. The above relationship can further suppress the occurrence of image blur.

[0190] The particle size is larger than the median diameter D of Si-doped strontium titanate particles. 50 The mass ratio of the silica particles in the entire silica particles is preferably 30 mass % to 100 mass %, more preferably 40 mass % to 100 mass %, and further preferably 50 mass % to 100 mass %.

[0191] The total amount of the silica particles added is preferably 1 to 10 parts by mass, more preferably 2 to 8 parts by mass, and further preferably 3 to 6 parts by mass, based on 100 parts by mass of the toner particles.

[0192] [Other additives]

[0193] The toner of the present embodiment may contain other external additives in addition to the Si-doped strontium titanate particles and the silica particles within a range that can obtain the effects of the present embodiment. Examples of other external additives include the following inorganic particles and resin particles.

[0194] As other external additives, for example, inorganic particles can be mentioned. As the inorganic particles, TiO 2 、Al 2 O 3 , CuO, ZnO, SnO 2 、CeO 2 , Fe 2 O 3 , MgO, BaO, CaO, K 2 O、Na 2 O, ZrO 2 、CaO·SiO 2 , K 2 O·(TiO 2 ) n 、Al 2 O 3 ·2SiO 2 、CaCO 3 MgCO 3 ,BaSO 4 MgSO 4wait.

[0195] The surface of the inorganic particles as an external additive is suitably subjected to hydrophobization. Hydrophobization is carried out by, for example, immersing the inorganic particles in a hydrophobization treatment agent. There is no particular limitation on the hydrophobization treatment agent, for example, silane coupling agents, silicone oils, titanate coupling agents, aluminum coupling agents, etc. can be cited. These treatment agents can be used alone or in combination of two or more. Relative to 100 parts by mass of inorganic particles, the amount of the hydrophobization treatment agent is generally less than 10 parts by mass or more than 10 parts by mass.

[0196] Other examples of the external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate, and melamine resin), cleaning lubricants (for example, particles of a fluorine-based high molecular weight body), and the like.

[0197] When the toner of the present embodiment contains other external additives, the amount of the other external additives added is preferably 0.01 mass % to 2.0 mass %, and more preferably 0.1 mass % to 1.0 mass %, based on the entire toner.

[0198] [Toner Manufacturing Method]

[0199] The toner according to the present embodiment is obtained by manufacturing toner particles and then adding an external additive to the toner particles.

[0200] The toner particles can be produced by any of dry methods (e.g., kneading and pulverization methods) and wet methods (e.g., aggregation and merging methods, suspension polymerization methods, dissolution and suspension methods, etc.). These methods are not particularly limited, and known methods can be used. Among these, the toner particles can be obtained by the aggregation and merging method (aggregation method).

[0201] Specifically, for example, in the case of manufacturing toner particles by an agglomeration and merging method, the toner particles are manufactured through the following steps: a step of preparing a resin particle dispersion in which resin particles serving as a binding resin are dispersed (resin particle dispersion preparation step); a step of agglomerating resin particles (and other particles if necessary) in the resin particle dispersion (in a dispersion after mixing other particle dispersions if necessary) to form agglomerated particles (agglomerated particle formation step); and a step of heating the agglomerated particle dispersion in which the agglomerated particles are dispersed to fuse / merge the agglomerated particles to form toner particles (fusion / merging step).

[0202] The details of each step are described below.

[0203] In the following description, a method for obtaining toner particles containing a colorant and a release agent is described, but the colorant and the release agent are additives used as needed. Of course, other additives besides the colorant and the release agent may also be used.

[0204] - Resin particle dispersion preparation step -

[0205] A resin particle dispersion in which resin particles as a binder resin are dispersed is prepared, and at the same time, for example, a colorant particle dispersion in which colorant particles are dispersed and a release agent particle dispersion in which release agent particles are dispersed are prepared.

[0206] The resin particle dispersion is prepared, for example, by dispersing the resin particles in a dispersion medium using a surfactant.

[0207] Examples of the dispersion medium used for the resin particle dispersion include aqueous media.

[0208] Examples of the aqueous medium include water such as distilled water and ion-exchanged water, alcohols, etc. These media may be used alone or in combination of two or more.

[0209] Examples of surfactants include anionic surfactants such as sulfate ester salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols; and the like. Among these, anionic surfactants and cationic surfactants can be particularly mentioned. Nonionic surfactants can also be used in combination with anionic surfactants or cationic surfactants.

[0210] The surfactant may be used alone or in combination of two or more.

[0211] In the resin particle dispersion, as a method for dispersing the resin particles in the dispersion medium, for example, a common dispersion method using a rotary shearing homogenizer or a ball mill, sand mill, bead mill, etc. with a medium can be cited. In addition, depending on the type of resin particles, the resin particles can also be dispersed in the dispersion medium using a phase inversion emulsification method. The phase inversion emulsification method is a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent that can dissolve the resin, a base is added to the organic continuous phase (O phase) for neutralization, and then an aqueous medium (W phase) is added to thereby invert the phase from W / O to O / W, so that the resin is dispersed in the aqueous medium in a particle form.

[0212] The volume average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably 0.01 μm or more and 1 μm or less, more preferably 0.08 μm or more and 0.8 μm or less, and further preferably 0.1 μm or more and 0.6 μm or less.

[0213] The volume average particle size of the resin particles is determined by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (e.g., LA-700 manufactured by Horiba, Ltd.). For the divided particle size range (segment), a cumulative distribution is plotted for volume from the small particle size side, and the particle size at the cumulative 50% point relative to all particles is measured, which is taken as the volume average particle size D50v. The volume average particle size of particles in other dispersions is measured in the same manner.

[0214] The content of the resin particles contained in the resin particle dispersion is preferably 5% by mass or more and 50% by mass or less, and more preferably 10% by mass or more and 40% by mass or less.

[0215] For example, a colorant particle dispersion and a release agent particle dispersion are prepared in the same manner as the resin particle dispersion. That is, the volume average particle size of the particles in the resin particle dispersion, the dispersion medium, the dispersion method, and the content of the particles are the same for the colorant particles dispersed in the colorant particle dispersion and the release agent particles dispersed in the release agent particle dispersion.

[0216] - Agglomerated Particle Formation Step-

[0217] Next, the resin particle dispersion, the colorant particle dispersion, and the release agent particle dispersion are mixed.

[0218] Then, the resin particles, the colorant particles, and the release agent particles are heterogeneously aggregated in the mixed dispersion to form aggregated particles containing the resin particles, the colorant particles, and the release agent particles and having a diameter close to that of the target toner particles.

[0219] Specifically, for example, a coagulant is added to the mixed dispersion, and the pH of the mixed dispersion is adjusted to acidity (for example, pH 2 to 5), a dispersion stabilizer is added as needed, and then heated to a temperature close to the glass transition temperature of the resin particles (specifically, for example, the glass transition temperature of the resin particles is -30°C to the glass transition temperature of -10°C), so that the particles dispersed in the mixed dispersion are agglomerated to form agglomerated particles.

[0220] In the aggregated particle forming step, for example, a coagulant may be added at room temperature (e.g., 25° C.) while the mixed dispersion is stirred using a rotary shearing homogenizer, the pH of the mixed dispersion is adjusted to acidic (e.g., pH 2 to 5), a dispersion stabilizer may be added as needed, and then the mixture may be heated.

[0221] Examples of the coagulant include surfactants having opposite polarity to the surfactant contained in the mixed dispersion, inorganic metal salts, and divalent or higher metal complexes. When a metal complex is used as the coagulant, the amount of surfactant used is reduced and the charging characteristics are improved.

[0222] If necessary, an additive that forms a complex or similar bond with the metal ion of the coagulant may be used together with the coagulant. As the additive, a chelating agent is preferably used.

[0223] Examples of the inorganic metal salt include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide; and the like.

[0224] As the chelating agent, a water-soluble chelating agent can be used. Examples of the chelating agent include hydroxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid; aminocarboxylic acids such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA); and the like.

[0225] The amount of the chelating agent added is preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, based on 100 parts by mass of the resin particles.

[0226] - Fusion / Merge Steps-

[0227] Next, the aggregated particle dispersion in which the aggregated particles are dispersed is heated to, for example, a temperature above the glass transition temperature of the resin particles (for example, a temperature 10°C to 30°C higher than the glass transition temperature of the resin particles) to fuse / merge (fuse and unify) the aggregated particles to form toner particles.

[0228] Through the above steps, toner particles are obtained.

[0229] After obtaining a dispersion of aggregated particles dispersed therein, toner particles can be manufactured by the following steps: further mixing the dispersion of aggregated particles with a dispersion of resin particles dispersed therein, agglomerating the resin particles so as to further adhere to the surfaces of the aggregated particles to form second aggregated particles; and heating the second dispersion of aggregated particles dispersed therein to fuse / merge the second aggregated particles to form toner particles with a core / shell structure.

[0230] After the fusion / merging step is completed, the toner particles formed in the solution are subjected to a known washing step, a solid-liquid separation step, and a drying step to obtain dry toner particles. Regarding the washing step, from the perspective of charging performance, replacement washing using ion exchange water can be fully implemented. Regarding the solid-liquid separation step, from the perspective of productivity, suction filtration, pressure filtration, etc. can be implemented. Regarding the drying step, from the perspective of productivity, freeze drying, airflow drying, fluidized bed drying, vibration fluidized bed drying, etc. can be implemented.

[0231] Thereafter, for example, an external additive is added to the obtained dry toner particles and mixed, thereby producing the toner of the present embodiment. The mixing can be performed using, for example, a V-type blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, coarse particles of the toner can be removed using a vibration sieving machine, a wind sieving machine, etc. as needed.

[0232] <Electrostatic Image Developer>

[0233] The electrostatic image developer according to the present embodiment includes at least the toner according to the present embodiment.

[0234] The electrostatic image developer of the present embodiment may be a one-component developer containing only the toner of the present embodiment, or may be a two-component developer in which the toner and a carrier are mixed.

[0235] The carrier is not particularly limited, and known carriers can be cited. Examples of the carrier include: a coated carrier in which a core material formed of magnetic powder is coated with a resin; a magnetic powder dispersion carrier in which magnetic powder is dispersed and mixed in a matrix resin; a resin impregnated carrier in which a porous magnetic powder is impregnated with a resin; and the like. The magnetic powder dispersion carrier and the resin impregnated carrier may also be a carrier in which the constituent particles of the carrier are used as a core material and the surface thereof is coated with a resin.

[0236] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt; and magnetic oxides such as ferrite and magnetite.

[0237] Examples of the coating resin and base resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylate copolymer, pure silicone resin or modified products thereof containing organic siloxane bonds, fluororesins, polyesters, polycarbonates, phenolic resins, epoxy resins, etc. The coating resin and base resin may contain other additives such as conductive particles. Examples of the conductive particles include particles of metals such as gold, silver, and copper, carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.

[0238] When the surface of the core material is coated with a resin, it can be enumerated as follows: a method of coating with a coating layer formed by dissolving a coating resin and various additives (used as needed) in an appropriate solvent, etc. The solvent is not particularly limited and can be selected by considering the type of resin used, coating suitability, etc.

[0239] Specific resin coating methods include: an immersion method, in which the core material is immersed in a coating layer forming solution; a spray method, in which the coating layer forming solution is sprayed onto the surface of the core material; a fluidized bed method, in which the coating layer forming solution is sprayed while the core material is suspended by flowing air; a kneading coater method, in which the core material of the carrier is mixed with the coating layer forming solution in a kneading coater and then the solvent is removed; and the like.

[0240] The mixing ratio (mass ratio) of the toner and the carrier in the two-component developer is preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100.

[0241] <Image Forming Apparatus, Image Forming Method>

[0242] The image forming device of the present embodiment comprises: an image holder; a charging mechanism for charging the surface of the image holder; an electrostatic image forming mechanism for forming an electrostatic image on the surface of the charged image holder; a developing mechanism for storing an electrostatic image developer and developing the electrostatic image formed on the surface of the image holder into a toner image using the electrostatic image developer; a transfer mechanism for transferring the toner image formed on the surface of the image holder to the surface of a recording medium; and a fixing mechanism for fixing the toner image transferred to the surface of the recording medium. The electrostatic image developer of the present embodiment is used as the electrostatic image developer.

[0243] The image forming device of the present embodiment implements an image forming method (the image forming method of the present embodiment), which has the following steps: a charging step, charging the surface of the image retaining body; an electrostatic image forming step, forming an electrostatic image on the surface of the charged image retaining body; a developing step, developing the electrostatic image formed on the surface of the image retaining body into a toner image using the electrostatic image developer of the present embodiment; a transfer step, transferring the toner image formed on the surface of the image retaining body to the surface of the recording medium; and a fixing step, fixing the toner image transferred to the surface of the recording medium.

[0244] The image forming device of this embodiment is applicable to the following well-known image forming devices: a device using a direct transfer method for directly transferring a toner image formed on the surface of an image holder to a recording medium; a device using an intermediate transfer method for transferring a toner image formed on the surface of an image holder to the surface of an intermediate transfer body for the first time, and transferring the toner image transferred to the surface of the intermediate transfer body to the surface of a recording medium for a second time; a device having a cleaning mechanism for cleaning the surface of the image holder after the toner image is transferred and before charging; a device having a de-staticizing mechanism for de-staticizing the surface of the image holder by irradiating de-staticizing light to the surface of the image holder after the toner image is transferred and before charging; and the like.

[0245] When the image forming device of the present embodiment is an intermediate transfer type device, the transfer mechanism used is, for example, a structure having the following components: an intermediate transfer body to the surface of which the toner image is transferred; a primary transfer mechanism that transfers the toner image formed on the surface of the image retaining body to the surface of the intermediate transfer body for the first time; and a secondary transfer mechanism that transfers the toner image transferred to the surface of the intermediate transfer body to the surface of the recording medium for the second time.

[0246] In the image forming apparatus of this embodiment, for example, the part including the developing mechanism may be a cartridge structure (processing cartridge) that is detachable from the image forming apparatus. As the processing cartridge, for example, a processing cartridge that stores the electrostatic image developer of this embodiment and has a developing mechanism is preferably used.

[0247] An example of the image forming apparatus according to the present embodiment is shown below, but the present invention is not limited thereto. In the following description, the main parts shown in the drawings are described, and the other descriptions are omitted.

[0248] Figure 1 2 is a diagram schematically showing the structure of the image forming apparatus according to the present embodiment.

[0249] Figure 1 The image forming apparatus shown in the figure is provided with first to fourth image forming units 10Y, 10M, 10C, 10K (image forming mechanism) of the electrophotographic method for outputting images of yellow (Y), magenta (M), cyan (C), and black (K) colors based on color separation image data. These image forming units (hereinafter sometimes referred to as "units") 10Y, 10M, 10C, 10K are arranged in parallel with each other at a predetermined distance in the horizontal direction. These units 10Y, 10M, 10C, 10K may be process cartridges that are detachable from the image forming apparatus.

[0250] Above each unit 10Y, 10M, 10C, 10K, an intermediate transfer belt (an example of an intermediate transfer body) 20 is extended through each unit. The intermediate transfer belt 20 is wound around a driving roller 22 and a supporting roller 24 so as to run in a direction from the first unit 10Y to the fourth unit 10K. The supporting roller 24 is biased in a direction away from the driving roller 22 by a spring (not shown) or the like, and tension is applied to the intermediate transfer belt 20 wound around the two. An intermediate transfer body cleaning device 30 is provided on the image holding body side of the intermediate transfer belt 20 so as to face the driving roller 22.

[0251] Yellow, magenta, cyan and black toners stored in toner cartridges 8Y, 8M, 8C and 8K are supplied to developing devices (an example of developing mechanisms) 4Y, 4M, 4C and 4K of the respective units 10Y, 10M, 10C and 10K.

[0252] The first to fourth units 10Y, 10M, 10C, and 10K have the same configuration and operation, and therefore the first unit 10Y disposed on the upstream side in the running direction of the intermediate transfer belt and forming a yellow image will be described as a representative.

[0253] The first unit 10Y has a photoreceptor 1Y that functions as an image holder. The following are arranged in order around the photoreceptor 1Y: a charging roller (an example of a charging mechanism) 2Y that charges the surface of the photoreceptor 1Y to a preset potential; an exposure device (an example of an electrostatic image forming mechanism) 3 that forms an electrostatic image by exposing the charged surface using a laser beam 3Y based on a color separation image signal; a developing device (an example of a developing mechanism) 4Y that supplies the charged toner to the electrostatic image to develop the electrostatic image; a primary transfer roller 5Y (an example of a primary transfer mechanism) that transfers the developed toner image to the intermediate transfer belt 20; and a photoreceptor cleaning device (an example of a cleaning mechanism) 6Y that removes the toner remaining on the surface of the photoreceptor 1Y after the primary transfer.

[0254] The primary transfer roller 5Y is arranged inside the intermediate transfer belt 20 and is provided at a position facing the photosensitive body 1Y. The primary transfer rollers 5Y, 5M, 5C, and 5K of each unit are connected to bias power supplies (not shown) for applying primary transfer bias. Each bias power supply changes the value of the transfer bias applied to each primary transfer roller under the control of a control unit (not shown).

[0255] Next, the operation of forming a yellow image in the first unit 10Y will be described.

[0256] First, before the operation, the surface of the photoreceptor 1Y is charged to a potential of -600 V to -800 V by the charging roller 2Y.

[0257] The photoreceptor 1Y has a conductivity (e.g., a volume resistivity of 1×10 -6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate with a resistance of 100 Ωcm or less. The photosensitive layer generally has a high resistance (resistance of a common resin), but has a property that the resistivity of the portion irradiated with the laser beam changes when the laser beam is irradiated. Therefore, according to the yellow image data sent from the control unit (not shown), the laser beam 3Y is irradiated from the exposure device 3 to the charged surface of the photoreceptor 1Y. As a result, an electrostatic image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.

[0258] The electrostatic image is an image formed on the surface of the photoreceptor 1Y by charging, which is a so-called negative latent image. The negative latent image is formed as follows: the resistivity of the irradiated portion of the photosensitive layer is reduced by using the laser beam 3Y, so that the charged charge on the surface of the photoreceptor 1Y flows; on the other hand, the charge of the portion not irradiated with the laser beam 3Y remains, thereby forming the negative latent image.

[0259] The electrostatic image formed on the photoreceptor 1Y rotates to a preset development position as the photoreceptor 1Y runs. At the development position, the electrostatic image on the photoreceptor 1Y is developed into a toner image by the developing device 4Y and visualized.

[0260] The developing device 4Y stores an electrostatic image developer containing, for example, at least a yellow toner and a carrier. The yellow toner is frictionally charged by being stirred inside the developing device 4Y, and has a charge of the same polarity (negative polarity) as the charge charged on the photoreceptor 1Y, and is held on the developer roller (an example of a developer holding member). After that, the surface of the photoreceptor 1Y passes through the developing device 4Y, whereby the yellow toner is electrostatically attached to the latent image portion on the surface of the photoreceptor 1Y that has been de-charged, and the latent image is developed using the yellow toner. The photoreceptor 1Y formed with the yellow toner image continues to run at a preset speed, and the toner image developed on the photoreceptor 1Y is conveyed to a preset primary transfer position.

[0261] When the yellow toner image on the photoreceptor 1Y is transported to the primary transfer position, a primary transfer bias is applied to the primary transfer roller 5Y, and the electrostatic force from the photoreceptor 1Y toward the primary transfer roller 5Y acts on the toner image, so that the toner image on the photoreceptor 1Y is transferred to the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and is controlled to, for example, +10 μA by a control section (not shown) in the first unit 10Y.

[0262] On the other hand, the toner remaining on the photoreceptor 1Y is removed and recovered by the photoreceptor cleaning device 6Y.

[0263] The primary transfer bias applied to the primary transfer rollers 5M, 5C, and 5K after the second unit 10M is also controlled in accordance with the first unit.

[0264] In this way, the intermediate transfer belt 20 to which the yellow toner image has been transferred by the first unit 10Y is sequentially conveyed through the second to fourth units 10M, 10C, and 10K, so that the toner images of the respective colors are multi-transferred in a superimposed manner.

[0265] The intermediate transfer belt 20 to which the four-color toner image has been multi-transferred by the first to fourth units arrives at the secondary transfer section, which is composed of the intermediate transfer belt 20, the support roller 24 in contact with the inner surface of the intermediate transfer belt, and the secondary transfer roller (an example of the secondary transfer mechanism) 26 arranged on the image holding surface side of the intermediate transfer belt 20. On the other hand, the recording paper (an example of the recording medium) P is fed to the gap between the secondary transfer roller 26 and the intermediate transfer belt 20 by the feeding member at a preset timing, and a secondary transfer bias is applied to the support roller 24. The transfer bias applied at this time has the same (-) polarity as the polarity (-) of the toner, and the electrostatic force from the intermediate transfer belt 20 to the recording paper P acts on the toner image, so that the toner image on the intermediate transfer belt 20 is transferred to the recording paper P. The secondary transfer bias at this time is determined based on the resistance detected by the resistance detection mechanism (not shown) that detects the resistance of the secondary transfer section, and the voltage is controlled.

[0266] Thereafter, the recording paper P is fed into a pressure-contact portion (nip portion) of a pair of fixing rollers in a fixing device (an example of a fixing mechanism) 28 , and the toner image is fixed on the recording paper P to form a fixed image.

[0267] Examples of the recording paper P to which the toner image is transferred include plain paper used in electrophotographic copy machines, printers, and the like. Examples of the recording medium include, in addition to the recording paper P, OHP transparent films and the like.

[0268] In order to further improve the smoothness of the image surface after fixing, the surface of the recording paper P is preferably smooth. For example, coated paper obtained by coating the surface of ordinary paper with a resin or the like, art paper for printing, etc. are preferably used.

[0269] The recording paper P on which the color image has been fixed is sent to the discharge portion, and a series of color image forming operations are completed.

[0270] <Process Cartridge, Toner Cartridge>

[0271] The process cartridge of the present embodiment is a process cartridge that is detachably mounted in an image forming apparatus and includes a developing mechanism that stores the electrostatic image developer of the present embodiment and develops the electrostatic image formed on the surface of the image holding member into a toner image using the electrostatic image developer.

[0272] The process cartridge of this embodiment is not limited to the above-described configuration, and may include a developing mechanism and, if necessary, at least one of other mechanisms selected from, for example, an image holding member, a charging mechanism, an electrostatic image forming mechanism, and a transfer mechanism.

[0273] An example of the process cartridge according to the present embodiment is shown below, but the present invention is not limited thereto. In the following description, the main parts shown in the drawings are described, and the description of other parts is omitted.

[0274] Figure 2 1 is a schematic diagram showing the structure of the process cartridge according to the present embodiment.

[0275] Figure 2 The processing box 200 shown is constructed by, for example, utilizing a housing 117 having a mounting guide 116 and an opening 118 for exposure to integrally combine and retain a photosensitive body 107 (an example of an image holding body) and a charging roller 108 (an example of a charging mechanism) provided around the photosensitive body 107, a developing device 111 (an example of a developing mechanism), and a photosensitive body cleaning device 113 (an example of a cleaning mechanism) to form an ink cartridge.

[0276] Figure 2 109 denotes an exposure device (an example of an electrostatic image forming mechanism), 112 denotes a transfer device (an example of a transfer mechanism), 115 denotes a fixing device (an example of a fixing mechanism), and 300 denotes recording paper (an example of a recording medium).

[0277] The toner cartridge of the present embodiment stores the toner of the present embodiment and is attached to and detached from the image forming apparatus. The toner cartridge stores replenishment toner to be supplied to a developing mechanism provided in the image forming apparatus.

[0278] Figure 1 The image forming apparatus shown is an image forming apparatus having a structure of attaching and detaching toner cartridges 8Y, 8M, 8C, and 8K, and the developing devices 4Y, 4M, 4C, and 4K are connected to the toner cartridges corresponding to the respective developing devices (colors) by toner supply pipes not shown. When the toner stored in the toner cartridge is insufficient, the toner cartridge is replaced.

[0279] Example

[0280] The embodiments disclosed in the examples are described in detail below, but the disclosed embodiments are not limited to these examples. In the following description, "parts" and "%" are based on mass unless otherwise specified.

[0281] <Production of Toner Particles>

[0282] [Preparation of amorphous polyester resin dispersion (A1)]

[0283]

[0284] The above materials were placed in a flask equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor and a distillation tower, and the temperature was raised to 210°C in 1 hour under a nitrogen flow. 1 part of tetraethoxytitanium was added to 100 parts of the above materials in total. The temperature was raised to 240°C in 0.5 hours while distilling off the generated water. After the dehydration condensation reaction was continued at 240°C for 1 hour, the reactant was cooled. In this way, an amorphous polyester resin with a weight average molecular weight of 94,500 and a glass transition temperature of 61°C was obtained.

[0285] After 40 parts of ethyl acetate and 25 parts of 2-butanol were added to a container equipped with a temperature control mechanism and a nitrogen replacement mechanism to prepare a mixed solvent, 100 parts of amorphous polyester resin were slowly added to dissolve it, and a 10% aqueous ammonia solution (equivalent to 3 times the amount of the acid value of the resin in terms of molar ratio) was added thereto and stirred for 30 minutes. Next, the container was replaced with dry nitrogen, the temperature was maintained at 40°C, and 400 parts of ion exchange water were added dropwise to the mixed solution while stirring it for emulsification. After the addition was completed, the emulsion was returned to 25°C to obtain a resin particle dispersion in which resin particles with a volume average particle size of 210 nm were dispersed. Ion exchange water was added to the resin particle dispersion to adjust the solid content to 20%, thereby preparing an amorphous polyester resin dispersion (A1).

[0286] [Preparation of Crystalline Polyester Resin Dispersion (B1)]

[0287]

[0288] The above materials were added to a three-necked flask after heating and drying, and the air in the three-necked flask was replaced with nitrogen to form an inert atmosphere. The mixture was stirred and refluxed at 180°C for 5 hours by mechanical stirring. Then, the temperature was slowly raised to 240°C under reduced pressure and stirred for 2 hours. After the mixture became viscous, it was air-cooled to stop the reaction. In this way, a crystalline polyester resin with a weight average molecular weight of 9700 and a melting temperature of 84°C was obtained.

[0289] 90 parts of crystalline polyester resin, 1.8 parts of anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., NEOGENRK) and 210 parts of ion exchange water were mixed, heated to 100°C, dispersed using a homogenizer (ULTRA-TURRAXT50 manufactured by IKA), and then dispersed for 1 hour using a pressure discharge type Gaulin homogenizer to obtain a resin particle dispersion in which resin particles having a volume average particle size of 205 nm were dispersed. Ion exchange water was added to the resin particle dispersion to adjust the solid content to 20%, thereby forming a crystalline polyester resin dispersion (B1).

[0290] [Preparation of Release Agent Particle Dispersion (W1)]

[0291] Solid paraffin wax (HNP-9 manufactured by Nippon Seira Co., Ltd.): 100 parts

[0292] Anionic surfactant (Neogen RK, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.): 1 part

[0293] Ion exchange water: 350 parts

[0294] The above materials were mixed and heated to 100°C, dispersed using a homogenizer (ULTRA-TURRAXT50 manufactured by IKA), and then dispersed using a pressure-dispensing Gaulin homogenizer to obtain a release agent particle dispersion in which release agent particles having a volume average particle size of 200 nm were dispersed. Ion-exchanged water was added to the release agent particle dispersion to adjust the solid content to 20%, thereby forming a release agent particle dispersion (W1).

[0295] [Preparation of Colorant Particle Dispersion Liquid (K1)]

[0296] Carbon black (Regal 330 manufactured by Cabot Corporation): 50 parts

[0297] Anionic surfactant NEOGEN RK (Daiichi Kogyo Seiyaku Co., Ltd.): 5 parts

[0298] Ion exchange water: 195 parts

[0299] The above materials were mixed and dispersed at 240 MPa for 10 minutes using an Ultimaizer (manufactured by Sugino Machine Co., Ltd.) to obtain a colorant particle dispersion (K1) having a solid content of 20%.

[0300] [Preparation of Toner Particles]

[0301]

[0302] The above materials were placed in a round stainless steel flask, 0.1N nitric acid was added to adjust the pH to 3.5, and then an aqueous solution of polyaluminum chloride was added by dissolving 2 parts of polyaluminum chloride (manufactured by Oji Paper Co., Ltd., 30% powder) in 30 parts of ion exchange water. After dispersion at 30°C using a homogenizer (ULTRA-TURRAXT50 manufactured by IKA), it was heated to 45°C in a heating oil bath and maintained until the volume average particle size reached 4.9μm. Next, 60 parts of amorphous polyester resin dispersion (A1) were added and maintained for 30 minutes. Then, after the volume average particle size reached 5.2μm, 60 parts of amorphous polyester resin dispersion (A1) were further added and maintained for 30 minutes. Next, 20 parts of a 10% NTA (nitrilotriacetic acid) metal salt aqueous solution (Chelest 70, manufactured by Chelest Co., Ltd.) were added, and a 1N sodium hydroxide aqueous solution was added to adjust the pH to 9.0. Next, 1 part of anionic surfactant (Tayca Power) was added, and the mixture was heated to 85° C. and maintained for 5 hours while being stirred. Then, the mixture was cooled to 20° C. at a rate of 20° C. / min. Then, the mixture was filtered, washed thoroughly with ion exchange water, and dried to obtain toner particles (1) having a volume average particle size of 5.7 μm and an average circularity of 0.971.

[0303] <Preparation of Strontium Titanate Particles>

[0304] [Preparation of Si-doped strontium titanate particles (1)]

[0305] Take TiO 2 0.7 mol of desulfurized and debonded metatitanic acid as a titanium source was added to the reaction vessel. Next, 0.77 mol of strontium chloride aqueous solution was added to the reaction vessel to make the Sr / Ti molar ratio 1.1. Next, silicon dioxide was dissolved in nitric acid and the resulting solution was added to the reaction vessel in an amount of 1 mol of Si per 100 mol of strontium. The initial TiO in the mixed solution of the three materials was 2The concentration is 0.75 mol / L. Next, the mixed solution is stirred, and the mixed solution is heated to 90°C. While the liquid temperature is maintained at 90°C and stirred, 153 mL of a 10N sodium hydroxide aqueous solution is added over 2 hours, and the liquid temperature is maintained at 90°C and stirred for 1 hour. Next, the reaction solution is cooled to 40°C, hydrochloric acid is added until the pH reaches 5.5, and stirring is performed for 1 hour. Next, the precipitate is washed by repeated decantation and redispersion in water. Hydrochloric acid is added to the slurry containing the washed precipitate, and the pH is adjusted to 6.5. The solid-liquid separation is performed by filtration, and the solid component is dried. To the dried solid component, an isobutyltrimethoxysilane ethanol solution in an amount of 20 parts relative to 100 parts of isobutyltrimethoxysilane is added, and the mixture is stirred for 1 hour. The solid-liquid separation is performed by filtration, and the solid component is dried in an atmosphere at 130°C for 7 hours to obtain Si-doped strontium titanate particles (1).

[0306] [Preparation of Si-doped strontium titanate particles (2) to (8)]

[0307] Si-doped strontium titanate particles (2) to (8) were prepared in the same manner as the preparation of the Si-doped strontium titanate particles (1), with the amount of Si added per 100 mol of strontium and / or the time for adding the 10N sodium hydroxide aqueous solution being changed as shown in Table 1.

[0308] The median diameter D of each of the Si-doped strontium titanate particles (1) to (8) was measured by the above method. 50 and Si doping amount (molar amount of Si relative to molar amount of Sr, mol %).

[0309] [Preparation of strontium titanate particles (9)]

[0310] Strontium titanate particles (9) were prepared in the same manner as the Si-doped strontium titanate particles (1) except that no Si source was added.

[0311] [Table 1]

[0312]

[0313] <Production of Silica Particles>

[0314] Silica particles were prepared by a sol-gel method or a vapor phase method, subjected to a hydrophobic treatment, and classified as necessary to obtain the silica particles shown in Table 2. The water content of the sol-gel silica particles was controlled by adjusting the temperature and time of the drying treatment after the hydrophobic treatment.

[0315] [Table 2]

[0316]

[0317] In Table 2, "HMDS" is 1,1,1,3,3,3-hexamethyldisilazane. "Monodisperse" means a particle size distribution that is unimodal and has a coefficient of variation of 20% or less. In the silica particles (1) to (7) produced by the sol-gel method, the coefficient of variation of the particle size distribution is 15% or less. The particle size distribution of the silica particles (9) has a peak at 120 nm and a smaller diameter side, and the proportion of silica particles constituting the peak of 120 nm is large.

[0318] <Preparation of carrier>

[0319] 14 parts of toluene, 2 parts of styrene-methyl methacrylate copolymer (polymerization mass ratio 90:10, weight average molecular weight 80,000) and 0.2 parts of carbon black (R330 manufactured by Cabot Corporation) were mixed and stirred for 10 minutes using a stirrer to prepare a dispersion. Next, the dispersion and 100 parts of ferrite particles (volume average particle size 36 μm) were charged into a vacuum degassing kneader, stirred at 60° C. for 30 minutes, and then degassed under reduced pressure under heating to dry the mixture to obtain a carrier.

[0320] <Example 1>

[0321] To 100 parts of the toner particles (1), Si-doped strontium titanate particles (1) and silicon dioxide particles (1) were added in the amounts shown in Table 3, and the mixture was placed in a sample mill and mixed at 10,000 rpm for 30 seconds. The mixture was then sieved using a vibrating sieve with a mesh size of 45 μm to prepare a toner having a volume average particle size of 5.7 μm.

[0322] The toner and the carrier were charged into a V-type blender at a ratio of toner:carrier=5:95 (mass ratio), and stirred for 20 minutes to obtain a developer.

[0323] <Examples 2 to 36, Comparative Examples 1 to 20>

[0324] A toner and a developer were obtained in the same manner as in Example 1 except that the type and amount of strontium titanate particles and the type and amount of silica particles added were changed according to the specifications shown in Tables 3 and 4.

[0325] <Performance Evaluation>

[0326] [Blurred image]

[0327] The toner cartridge of each example was filled with the toner and installed in an image forming apparatus (a modified version of ApeosPort-IV C5575 manufactured by Fuji Xerox Co., Ltd.). The developer of each example was filled in a developing device of the image forming apparatus.

[0328] The image was left in an environment of 30°C and 85% relative humidity for 24 hours, and then, 100,000 images with an image density of 1% were formed on A4-size paper at a rate of one sheet per 120 seconds.

[0329] Next, place the image in an environment of 10°C / 15% relative humidity for 24 hours. After placing, form 10 images with an image density of 40% on A4-sized paper in succession. Observe the 10 images with the naked eye and a magnifying glass with a magnification of 5 times, and grade the blurring of the images according to the following criteria.

[0330] G1: No image blur was observed on all 10 sheets.

[0331] G2: Slight image blur was observed with a magnifying glass on one image, but it was not a problem.

[0332] G3: Slight image blur was observed using a magnifying glass on many images, but it was so slight that it did not hinder practical use.

[0333] G4: The images are blurred as observed by naked eyes on many images, which is not suitable for practical use.

[0334] G5: All 10 images were observed to be blurred with the naked eye, which is not suitable for practical use.

[0335] [Powder mist amount (クラウド amount)]

[0336] Using a mending tape, the upper cover of the developer after the above-mentioned imaging was transferred to an OHP transparent film. The density of the mending tape after the transfer was measured at 8 points at equal intervals using an image densitometer X-Rite938 (manufactured by X-Rite). The difference between the measured result and the density of the mending tape alone was quantitatively calculated as the powder mist amount. The powder mist amount was graded according to the following criteria based on the concentration of the maximum value. G1 to G3 are suitable for practical application.

[0337] G1: 0≦Δconcentration≦0.2

[0338] G2: 0.2<Δconcentration≦0.4

[0339] G3: 0.4<Δconcentration≦0.6

[0340] G4: 0.6<Δconcentration≦0.8

[0341] G5: 0.8<Δ concentration

[0342] Regarding the "particle size D" in Table 3, when two or three types of silica particles are used, it is larger than the median diameter D of the strontium titanate particles. 50 and is closest to the median diameter D 50Regarding the "external addition amount M2" in Table 3, the peak diameter is greater than the median diameter D of the strontium titanate particles. 50 The total amount of silica particles added.

[0343] The “is there a value greater than the median diameter D 50 The peak "in the particle size distribution of silica particles" refers to whether there is a peak larger than the median diameter D of strontium titanate particles. 50 The peak.

[0344]

[0345]

Claims

1. A toner for electrostatic image development, wherein: The toner contains toner particles, Si-doped strontium titanate particles and silicon dioxide particles. The particle size D of at least one peak in the particle size distribution based on the number of primary particles of the silicon dioxide particles is larger than the median diameter D based on the number of primary particles of the Si-doped strontium titanate particles. 50 , The molar amount of Si contained in the Si-doped strontium titanate particles is 0.25 mol% or more and 10 mol% or less relative to the molar amount of Sr, The median diameter D of the Si-doped strontium titanate particles is 50 The particle size D of at least one peak in the particle size distribution based on the number of primary particles of the silica particles satisfies 10 nm ≤ DD 50 ≦100nm.

2. The electrostatic image developing toner according to claim 1, wherein The molar amount of Si contained in the Si-doped strontium titanate particles is 1 mol% to 5 mol% relative to the molar amount of Sr.

3. The electrostatic image developing toner according to claim 1 or 2, wherein The median diameter D of the Si-doped strontium titanate particles is 50 It is greater than 30nm and less than 80nm.

4. The electrostatic image developing toner according to claim 3, wherein The median diameter D of the Si-doped strontium titanate particles is 50 It is greater than 30nm and less than 60nm.

5. The electrostatic image developing toner according to claim 1 or 2, wherein The particle size D of the silica particles is not less than 40 nm and not more than 120 nm.

6. The electrostatic image developing toner according to claim 5, wherein The particle size D of the silica particles is not less than 60 nm and not more than 110 nm.

7. The electrostatic image developing toner according to claim 1, wherein The median diameter D of the Si-doped strontium titanate particles is 50 The particle size D of at least one peak in the particle size distribution based on the number of primary particles of the silica particles satisfies 20 nm ≤ DD 50 ≦90nm.

8. The electrostatic image developing toner according to claim 1 or 2, wherein The silica particles include sol-gel silica particles. The particle size D of at least one peak composed of sol-gel silica particles in the particle size distribution based on the number of primary particles of the silica particles is larger than the median diameter D based on the number of primary particles of the Si-doped strontium titanate particles. 50 .

9. The electrostatic image developing toner according to claim 8, wherein The median diameter D of the Si-doped strontium titanate particles is 50 The particle size D of at least one peak formed by the sol-gel silica particles satisfies 10 nm ≤ DD 50 ≦100nm.

10. The electrostatic image developing toner according to claim 8, wherein The water content of the sol-gel silica particles is 1 mass % or more and 10 mass % or less.

11. The electrostatic image developing toner according to claim 1 or 2, wherein The content M1 of the Si-doped strontium titanate particles and the particle size are greater than the median diameter D of the Si-doped strontium titanate particles. 50 The content M2 of the silica particles satisfies the relationship of 1.2≦M2 / M1≦5.0 on a mass basis. 12 . An electrostatic image developer comprising the electrostatic image developing toner according to claim 1 . 13 . A toner cartridge that is detachably mounted in an image forming apparatus, the toner storing the electrostatic image developing toner according to claim 1 .

Citation Information

Patent Citations

  • Electrophotographic toner and method for manufacturing same

    JP2005148405A

  • Image forming apparatus

    JP2011203758A

  • Toner and method for manufacturing toner

    JP2018200395A

  • Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method

    JP2019028235A

  • Electrostatic charge image developing toner, electrostatic charge image developer, and toner cartridge

    CN109307990A